Evaluation of gravity-led and energy-fed drainage for sustaining food security in the polders of the coastal zone of Bangladesh - Mondal, Manoranjan K.; Yadav, Sudhir; Baidya, Bishwajit; Khan, Zahirul H.; Sutradhar, Asish; Humphreys, Elizabeth; Kamal, Farhana A.; Jagadish, Krishna S.V. (Wiley, 2022)
Bangladesh is currently self‐sufficient in rice production but faces immense challenges of sustaining that self‐sufficiency because of population growth and climate change. There is little scope to further increase cropping intensity except in the underutilized 1.2 Mha of lands enclosed in the polders of the coastal zone. The main impediment to wide‐scale adoption of more productive cropping systems in the polders is poor drainage that often results in waterlogging. Therefore, a study was conducted in polder 30, in the medium‐salinity region of the south‐west coastal zone, to examine the biophysical and economic feasibility of low‐cost gravity (gravity‐led) drainage. The results show a considerable opportunity to increase rice production in the polders with improved drainage practices. The feasibility of drainage through pumping (energy‐fed) was also assessed, given that there are already situations where gravity‐led drainage is not feasible, and these situations are likely to increase because of climate change‐induced sea level rise and the sinking of polder lands. Energy‐fed drainage was demonstrated to be profitable with a yield gain of at least 1.5 t/ha from just the wet season; further intensification to 50% of polder lands may yield an additional harvest of 3–6 million tons of rice per year. Therefore, investing in improved drainage management in the polders could be a major game changer in sustaining the food security of the nation, especially the climate‐vulnerable polder communities of Bangladesh.